Traumatic Abdominal Venous Injury: Diagnosis and Management - Abad-Santos, Matthew; Jeffries, James C.; Hua, Charles; Johnson, Guy E. (Digestive Disease Interventions, 2025)
The management of traumatic injury of the large veins within the abdomen has continued to evolve with the development of endovascular techniques and the innovation of technology. Operative management of these patients is often difficult due to the anatomic location of these injuries and other associated injuries. Venous injuries can range from acute hemorrhage to complete thrombosis of the vessel, posing high rates of morbidity and mortality. A comprehensive approach to trauma patients, including initial assessment and imaging, is important in detecting injuries to the inferior vena cava or portomesenteric veins and their tributaries. Patient presentation and prognosis are important factors that drive treatment options. This article will review traumatic injuries of the major veins within the abdomen and potential options for endovascular management.
Keywords: venous; trauma; abdomen; portal; mesenteric